A Matter of life and Death for Manitoba’s Children: An Overview of Birth Rates and Mortality Rates - Martens, Patricia J. (Can J Public Health, 2002)
OBJECTIVE: To determine the fertility and child mortality rates for Manitoba. METHODS: Fertility and mortality rates were derived from the Population Health Research Data Repository and Vital Statistics, for 1994 through 1998. Data are presented by 12 Regional Health Authorities (RHAs), 12 Winnipeg Community Areas (CAs) and by income quintile. Each indicator is correlated with PMR (the age- and sex-adjusted premature mortality rate, i.e., death before age 75) and SEFI (Socioeconomic Factor Index, a standardized composite index), both considered proxies for overall health and socioeconomic well-being of populations. RESULTS: Manitoba’s total fertility rate was 1.77 children per woman, ranging from 1.62 to 3.15 by RHA, and 1.21 to 2.30 by Winnipeg CA. Manitoba’s infant mortality rate was 6.6/1000 (or 5.5/1000 excluding <500 g or <20 weeks gestation), ranging from 4.5 to 10.2 by RHA (4.2 to 9.8 exclusive), and 3.7 to 8.4 by Winnipeg CA (2.7 to 6.7). There was a gradient of infant mortality by income quintile (p<0.001), with double the rate comparing lowest to highest. Child mortality rates varied geographically and by gender, with northern children at greatest risk. Injury was the leading cause of death (52% for ages 1 through 9, 75% for ages 15 to 19). CONCLUSION: Fertility rates, as well as infant and child mortality rates, were positively associated with PMR and SEFI, with substantial geographical variation.